Phenomenography: A methodology for information literacy research. (December 2016) - Forster, Marc
The qualitative methodology phenomenography has been successfully used to determine the range of information literacy experiences of defined groups and professions. Phenomenographic method is believed to yield research findings which give a richer and more accurate picture of what information literacy means in practical terms. The archetypal definitions of the limited but interrelated experiences of information literacy that a phenomenographic study provides have been used as a basis of evidence-based information literacy educational interventions (Andretta, 2007). What are the epistemological ideas behind phenomenography and what are the data collection and analysis procedures based on its philosophical underpinnings? The key principles as described in the literature are discussed in this paper, beginning with the early work of Marton (1986). The use of phenomenography to research information literacy experience began with Christine Bruce's (1997) seminal work. The value of the work of Bruce and her followers have been recently recognized by ACRL (2014).